Law‐Gospel theologies of a state of exception. Issue 1 (1st February 2021) - Carr, Amy; Helmer, Christine
Abstract: We address contemporary concerns with fascism by critically assessing the classic law/gospel relation in Lutheran theology. Karl Holl, founder of the Luther Renaissance in the early twentieth century, develops Luther's experience of the self under the divine wrath in terms that have affinity to what Carl Schmitt calls the "state of exception." We examine similar non‐dialectical ways of relating law/gospel that nourish fascist tendencies on the right or left in North America.